The Universe of Microbiome and how it Influences our Health Outcomes - Yadav, Jay Narayan; Ganguli, Aparna; Kaithal, Poonam (International Journal of Scientific Research in Biological Sciences, 2025)
The human microbiome consists of bacteria, archaea, viruses, and eukaryotes that inhabit both our internal and external environments. These microorganisms influence human physiology, affecting our health status, and can enhance or impair our metabolic and immune functions. Microbes can be found in many different places in the human body and have adapted to each location. For example, certain types of microbes are more common in the gastrointestinal tract, while others inhabit the respiratory tract, nasal cavity, and skin surface. The microbes that naturally live in the human body have become well-suited to interacting with the immune system over time. Changes in the microbial community in the intestines play a significant role in human health and the development of diseases. These changes can be due to lifestyle or the presence of an underlying disease. Imbalance in the microbiota can make the body more susceptible to infections, with the likelihood of infection depending on which part of the body is affected. The various kinds of microbes found in the human body have different metabolic activities and functions depending on their location. It is crucial to understand the composition and activities of the human microbiome in order to understand the impact on human health and disease.